THE IMPACTS OF THE TAMAN DAYU RESIDENCE DEVELOPMENT TO SELF-HELP HOUSING SURROUND IN EFFORTS TO CREATE ECOVILLAGE - Erinda Dwi Aryanti; Ispurwono Soemarno; Johan Silas (Journal of Architecture&ENVIRONMENT, 2012)
To respond to the rapid growth of residential area needs, the sub urban area become an alternative area of housing and business developments. The Taman Dayu, as a new residential developments in the middle of rural areas, assumingly brought several impacts to the human settlements. The things to consider is the impact on the self-help housing area nearby, whether the residential housing developments can assist the developments of the self-help housing area (kampung), or in contrary it will vanish the characteristics and life of rural settlements. This research describes the positive and negative impacts of the developments of The Taman Dayu Residence to rural settlements nearby. Furthermore, the potential concept which can be created by self-help housing will be formulated to create ecovillage. Exploratory methods is utilized with qualitative data analysis and presented descriptively by the consideration of progressing research which refers to the time sequence of The Taman Dayu Residence and settlement development nearby. The results of this research may give a positive and negative representation of a changes in residential environments, so as to the concept of potential optimization which is appropriate with existing conditions can be formulated by directing to the development of rural areas.